First record of the genus Tanybelus (Salticidae: Salticinae: Sarindini) from Colombia (2017)
A first record of the jumping spider genus Tanybelus (Salticidae: Salticinae: Sarindini) from Colombia is presented, with a new record of T. aeneiceps Simon, 1902 from the Cundinamarca department, in the municipalities of Albán and San Antonio de Tequendama. This is the first record of the species after its original description, more than 100 years ago. Additionally, diagnostic illustrations of the body and copulatory organs, a map with its known distribution and notes of its natural history are also given.